Multilevel voltage source inverter with optimised usage of bidirectional switches - Jamaludin, J.; Abd Rahim, N.; Ping, H.W. (Institution of Engineering and Technology (IET), 2015)
This study presents a multilevel voltage source inverter that has been designed to reduce circuit complexity by optimising the use of bidirectional switches. The proposed inverter is built by adding an auxiliary circuit comprising an arrangement of bidirectional switches to the three-phase, six-switch, full-bridge configuration. Several bidirectional switches are made to function in the optimised mode in which their operations are divided among the three phases. The presence of the optimised mode considerably reduces the number of power switches as the number of levels in the line-to-line voltage waveform increases. A novel modulation scheme based on space vector concept with virtual vectors utilisation has also been developed. A detailed study of the proposed inverter is described through the example of a five-level structure. The performance of the proposed inverter is analysed through MATLAB/SIMULINK simulation and verified via the practical tests conducted on a laboratory prototype with a DSP-based controller. A comparison is also made against classical multilevel inverters to complete the analysis.